Cell death paradigms in the pathogenesis of Mycobacterium tuberculosis infection - Parandhaman, Dinesh K.; Narayanan, Sujatha (Frontiers in Cellular and Infection Microbiology, 2014)
Cell death or senescence is a fundamental event that helps maintain cellular homeostasis, shapes the growth of organism, and provides protective immunity against invading pathogens. Decreased or increased cell death is detrimental both in infectious and non infectious diseases. Cell death is executed both by regulated enzymic reactions and non enzymic sudden collapse. In this brief review we have tried to summarize various cell death modalities and their impact on the pathogenesis of Mycobacterium tuberculosis